PBLRQA Strategy on Metacognitive Skills and Higher-order Thinking of Students in the Genetics Course - Hasan, Isharyadi; Budiarsa, I Made; Astija; Bialangi, Mursito S; Jamhari, Mohammad (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
Low metacognitive abilities and high-level thinking cause students to have difficulty understanding genetics course material. This research aims to analyze the effectiveness of PBLRQA, PBL, and RQA strategies on students' metacognitive and higher-order thinking skills. This research uses a non-equivalent control group pretest-posttest design. Sampling was carried out on 118 students consisting of four classes using saturated sampling techniques. The research instruments used were observation sheets on lecturer and student activities, essay-based metacognitive skills tests, and multiple-choice tests on high-level thinking skills. Lecturer and student activity data were analyzed based on the percentage of indicators categorized as high and very high syntactically. Data on metacognitive skills and higher-order thinking were analyzed using the Normalized Gain and Independent Kruskal Wallis tests. Research findings show that implementing PBLRQA, PBL, and RQA strategies is ineffective in improving students' metacognitive and higher-order thinking skills. To follow up on these findings, further research is needed to explore the involvement of learning styles and social support on students' metacognitive skills and higher-order thinking skills, focusing on implementing PBLRQA and RQA strategies.